2016
DOI: 10.1111/jopr.12432
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Gap of Milled versus Cast Gold Restorations

Abstract: Within the limitations of this study, results indicate that gold restorations milled with the tested parameters provide a vertical marginal gap that is an acceptable alternative to traditional gold crown casting techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…The marginal gap width was found to range from 24.2 to 29.5 µm in this study. There were no significant differences in marginal gap widths among the dental stones examined, and the marginal gap widths were in a similar range to those of previous studies [12][13][14] in which the shape of the abutment was slightly different but the gap widths of crowns made by the same casting alloy were reported to be approximately 30 µm. Although the present study found different amounts of setting expansion among the dental stones ( Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The marginal gap width was found to range from 24.2 to 29.5 µm in this study. There were no significant differences in marginal gap widths among the dental stones examined, and the marginal gap widths were in a similar range to those of previous studies [12][13][14] in which the shape of the abutment was slightly different but the gap widths of crowns made by the same casting alloy were reported to be approximately 30 µm. Although the present study found different amounts of setting expansion among the dental stones ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The present study examined the adaptability of cast crowns to abutments using working casts prepared with SM. Following the procedure reported in previous studies [12][13][14] , the gap widths between the crown margins and the shoulder margins of the abutments were measured. In order to clarify the difference between the dental stones used, the procedures for fabrication of cast crowns were identical for the experimental groups after taking the impression and preparing the working cast.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the type of material, adjustment of restorations before cementation is a matter of great importance and can determine the final internal and marginal discrepancies. [20][21][22] This study aimed to evaluate and compare the marginal and internal adaptations of crowns made of three different CAD/CAM materials before and after adjustment. The first null hypothesis was that there would be no difference between LDGC (IPS e.max CAD), ZLS (Vita Suprinity), and PICN (Vita Enamic) regarding marginal and internal adaptation of full-coverage restorations.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] In previous research, dental gold-based alloys showed wear characteristics very similar to human enamel. 1,2 Nevertheless, in spite of their excellent marginal accuracy 10,11 and uncontested mechanical/ tribological properties, 12 an increasing demand for better esthetics persuaded clinicians to withdraw full-gold restorations in favor of alternative toothcolored materials.…”
Section: Introductionmentioning
confidence: 99%